Chemical compositions and biological activities of Scutellaria pinnatifida A. Hamilt aerial parts - Abbas Delazar; Hossein Nazemiyeh; Fariba Heshmati Afshar; Niloofar Barghi; Solmaz Esnaashari; Parina Asgharian (Wolters Kluwer Medknow Publications, 2017)
Phytochemical analysis of the methanolic and dichloromethane extracts of the aerial parts of Scutellaria pinnatifida led to the isolation of a phenylpropanoid, 1-o-feruloyl-ß-D-glucose [1], two known flavonoids including luteolin-7-o-glucoside (2) and apigenin-7-o-glucoside (3), three known phenylethanoid glycosides composed of phlomisethanoside (4), syringalide A (5), and verbascoside (6), and oleic acid (7). Isolation and structural elucidation of compounds were accomplished by HPLC and spectroscopic methods (UV, 1H- NMR, 13C-NMR). The extracts were also evaluated for their radical scavenging activity and insecticidal property by 2,2-diphenyl-1-picryl-hydrazyl (DPPH) assay and contact toxicity method, respectively. Among the extracts, the methanol extract showed the most potent free radical scavenging activity with a RC50 value of 0.044 ± 0.350 mg/mL which could be attributed to the presence of the isolated phenolic compounds. In the case of insecticidal activity, the n-hexane extract displayed the most potent activity and caused 10%, 15%, and 40% mortality to Oryzaephilus mercator at the concentration of 5, 10, and 15 mg/mL after 4 h of exposure.